2021
DOI: 10.3389/fimmu.2021.639358
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Immunologic Correlates of Response to Pandemic Influenza Vaccine in Aviremic, HIV-Infected Children

Abstract: People living with HIV (PWH) often exhibit poor responses to influenza vaccination despite effective combination anti-retroviral (ART) mediated viral suppression. There exists a paucity of data in identifying immune correlates of influenza vaccine response in context of HIV infection that would be useful in improving its efficacy in PWH, especially in younger individuals. Transcriptomic data were obtained by microarray from whole blood isolated from aviremic pediatric and adolescent HIV-infected individuals (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Vaccine response was in fact extremely poor in our study compared to other series addressing also influenza immunization in children living with HIV ( 14 , 15 ). This fact is even more shocking taking into account the good immunological status of the children included in this pilot trial, as previous studies have suggested that immunological status determines vaccine response ( 7 , 32 ). The identification of predictors of vaccine response has been identified as an urgent need for this population that grows with the virus ( 32 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Vaccine response was in fact extremely poor in our study compared to other series addressing also influenza immunization in children living with HIV ( 14 , 15 ). This fact is even more shocking taking into account the good immunological status of the children included in this pilot trial, as previous studies have suggested that immunological status determines vaccine response ( 7 , 32 ). The identification of predictors of vaccine response has been identified as an urgent need for this population that grows with the virus ( 32 ).…”
Section: Discussionmentioning
confidence: 93%
“…This fact is even more shocking taking into account the good immunological status of the children included in this pilot trial, as previous studies have suggested that immunological status determines vaccine response (7,32). The identification of predictors of vaccine response has been identified as an urgent need for this population that grows with the virus (32). Markers available to routine clinical practice would allow us to personalize vaccination schedules.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the difference in immune responses between LAIV and inactivated vaccines can also be explained at the level of gene expression ( 124 ). de Armas et al even suggested to use transcriptional data as a correlate of vaccine response in HIV-infected children ( 125 ). A recent study demonstrates that influenza vaccines are also able to epigenetically remodel cells of the innate immune system (monocytes and dendritic cells) which is associated with a higher expression of antiviral genes ( 126 ).…”
Section: Methods To Assess Cell-mediated Immunitymentioning
confidence: 99%
“…In a cohort of perinatally infected children comparing treated and untreated patients, the number of memory B cells (cells that are recalled to proliferate and produce antibodies upon booster vaccination or re-exposure to pathogen) was not completely restored by ART ( McCarty et al, 2018 ), although this could improve through early initiation of ART ( Shalekoff et al, 2021 ). Reduced function of T follicular helper cells, which are critical for the differentiation of B cells into high-affinity antibody producers, correlates with poor response to an influenza vaccine in CWH who had undetectable HIV-1 virus ( de Armas et al, 2021 ). However, in CWH on antiretroviral treatment, the number of T follicular helper cells is partially restored ( McCarty et al, 2018 ).…”
Section: Impact Of Hiv Infection On Hpv and Other Vaccinationsmentioning
confidence: 99%